Deciphering Iron‐Dependent Activity in Oxygen Evolution Catalyzed by Nickel–Iron Layered Double Hydroxide. Issue 21 (11th March 2020) - Lee, Seunghwa; Bai, Lichen; Hu, Xile
Abstract: Nickel iron oxyhydroxide is the benchmark catalyst for the oxygen evolution reaction (OER) in alkaline medium. Whereas the presence of Fe ions is essential to the high activity, the functions of Fe are currently under debate. Using oxygen isotope labeling and operando Raman spectroscopic experiments, we obtain turnover frequencies (TOFs) of both Ni and Fe sites for a series of Ni and NiFe layered double hydroxides (LDHs), which are structurally defined samples of the corresponding oxyhydroxides. The Fe sites have TOFs 20–200 times higher than the Ni sites such that at an Fe content of 4.7 % and above the Fe sites dominate the catalysis. Higher Fe contents lead to larger structural disorder of the NiOOH host. A volcano‐type correlation was found between the TOFs of Fe sites and the structural disorder of NiOOH. Our work elucidates the origin of the Fe‐dependent activity of NiFe LDH, and suggests structural ordering as a strategy to improve OER catalysts. Abstract : Iron versus nickel : Turnover frequencies (TOFs) of both Ni and Fe sites in the oxygen evolution reaction (OER) catalyzed by a series of Ni and NiFe layered double hydroxides (LDHs) have been determined. Effects of structural disorder of NiOOH lattice are revealed.